Impact of shock chlorination on the chloramine content in the rehabilitation pool water - Wyczarska-Kokot, Joanna; Grübel, Klaudiusz (Instal, 2020)
The content of chloramines in swimming pool water, due to their negative impact on the health of swimmers and the staff of pool facilities, is obligatorily inspected once a day in pool water samples. The concentration of chloramines (combined chlorine), regardless of the function of the pool, should not be higher than 0.3 mgCl2/dm3. However, it is recommended to keep chloramines as low as possible, and in pools for special purposes, including in rehabilitation pools, it is recommended not to exceed 0.2 mgCl2/dm3. Despite the availability of various disinfectants and modern methods of water disinfection, the problem of high concentrations of chloramines in pool waters is still relevant. The main purpose of the research was to analyze the impact of sequentially applied shock chlorination on the chloramine content in the water of the rehabilitation pool. Analyzing physically, chemically and bacteriologically pool water samples the quality of water was assessed after each shock chlorination. There was a short-lasting reduction of the chloramine concentration to the value below 0.2 mgCl2/dm3 for several hours. An additional analysis of the impact of redox potential on the chloramines content showed that redox values above 750 mV also reduced chloramines.
Keywords: swimming pool water; shock chlorination; chloramines